High tolerance and physiological mechanism of Zymomonas mobilis to phenolic inhibitors in ethanol fermentation of corncob residue. Issue 9 (12th May 2015) - Gu, Hanqi; Zhang, Jian; Bao, Jie
ABSTRACT Corncob residue as the lignocellulosic biomass accumulated phenolic compounds generated from xylitol production industry. For utilization of this biomass, Zymomonas mobilis ZM4 was tested as the ethanol fermenting strain and presented a better performance of cell growth (2.8 × 108 CFU/mL) and ethanol fermentability (54.42 g/L) in the simultaneous saccharification and fermentation (SSF) than the typical robust strain Saccharomyces cerevisiae DQ1 (cell growth of 2.9 × 107 CFU/mL, ethanol titer of 48.6 g/L). The physiological response of Z. mobilis ZM4 to the twelve typical phenolic compounds derived from lignocellulose was assayed and compared with that of S. cerevisiae DQ1. Z. mobilis ZM4 showed nearly the same tolerance to the phenolic aldehydes with S. cerevisiae DQ1, but the stronger tolerance to the phenolic acids existing in corncob residue (2‐furoic acid, p‐hydroxybenzoic acid, p‐coumaric acid, vanillic acid, ferulic acid, and syringic acid). The tolerance mechanism of Z. mobilis was investigated in terms of inhibitor degradation, cell morphology and membrane permeability under the stress of phenolics using GC‐MS, scanning and transmission electron microscopies (SEM and TEM), as well as fluorescent probes. The results reveal that Z. mobilis ZM4 has the capability for in situ detoxification of phenolic aldehydes, and the lipopolysaccharide aggregation on the cell outer membrane of Z. mobilis ZM4 provided the permeable barrier to the attack of phenolic acids. Biotechnol. Bioeng. 2015;112: 1770–1782. © 2015 Wiley Periodicals, Inc.